1996
DOI: 10.1161/01.atv.16.6.749
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Testosterone in Men With Acute Ischemic Stroke

Abstract: Serum levels of total and free testosterone and 17 beta-estradiol were determined in 144 men with acute ischemic stroke and 47 healthy male control subjects. Blood samples from patients were drawn a mean of 3 days after stroke onset and also 6 months after admission in a subgroup of 45 patients. Initial stroke severity was assessed on the Scandinavian Stroke Scale and infarct size by computed tomographic scan. Mean total serum testosterone was 13.8 +/- 0.5 nmol/L in stroke patients and 16.5 +/- 0.7 nmol/L in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 41 publications
11
87
0
5
Order By: Relevance
“…Our findings are supported by a recent study finding lower levels of both total and free testosterone in men suffering acute ischemic stroke. However, a slight but not significant increase of hormone levels was noted at the 6-month followup, possibly suggesting in part an acute effect on the hypothalamic -pituitary-testicular axis (8). We also found lower levels of total and free testosterone in men with cancer, and a higher level of free testosterone in men with IHD.…”
Section: Variation With Chronic Diseasementioning
confidence: 47%
“…Our findings are supported by a recent study finding lower levels of both total and free testosterone in men suffering acute ischemic stroke. However, a slight but not significant increase of hormone levels was noted at the 6-month followup, possibly suggesting in part an acute effect on the hypothalamic -pituitary-testicular axis (8). We also found lower levels of total and free testosterone in men with cancer, and a higher level of free testosterone in men with IHD.…”
Section: Variation With Chronic Diseasementioning
confidence: 47%
“…Moreover, a decreased serum testosterone concentration has been shown to be associated with acute ischemic strokes, infarct size and mortality (17). These data suggest that normal testosterone levels may offer protection against the development of atherosclerosis in middle-aged men.…”
Section: European Journal Of Endocrinologymentioning
confidence: 82%
“…29 We found that serum testosterone levels decrease dramatically in all males after stroke, consistent with both previous clinical and animal studies. 30 This could be due to decreased production of testosterone (by the testes) or increased aromatizaton to estradiol in the brain, or both. Lower testicular expression of steroidogenesis-related genes has been reported after experimental stroke in rats.…”
Section: Discussionmentioning
confidence: 99%